(untitled) (Research, Society and Development, 2022)
Microbial resistance is a global problem and consequently it is necessary to intensively search for new antimicrobial and antifungal agents from natural sources, through the exploration of new niches and habitats. The beetles of the Passalidae family live and feed on decaying wood and their intestines are richly colonized by different microorganisms. Actinomycetes represent one of the important classes of bacteria for their ability to produce a wide range of secondary metabolites. 103 strains of actinomycetes were isolated. Moving on to the preliminary antimicrobial activity tests with the agar diffusion method, the top five being selected for further testing. Liquid fermentations were carried out with casein starch broth and CZAPEC and solid medium with potato-dextrose and starch agar. At the end of the fermentation processes, the cultures were subjected to extraction in ethyl acetate, obtaining the crude extracts, the material was filtered, concentrated and dried, and the yields were calculated. The extracts were analyzed for antimicrobial and antifungal activity and for the minimum inhibitory concentration using the microdilution technique. CCD thin layer chromatography was performed in the chloroform methanol ratio (70:30) to assess the complexity of the samples. Then the crude extract of the BA16.2.1 strain was selected as the most promising and proceeded to purification and isolation of active fractions in preparative HPLC in MS/MS. Through this study it is expected to obtain active and identified fractions regarding their antimicrobial and antifungal activity.